2018
DOI: 10.5152/turkpediatriars.2017.5312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of febrile neutropenic attacks of pediatric hematology-oncology patients

Abstract: Aim: Febrile neutropenia is an important cause of mortality and morbidity in hematology-oncology patients undergoing chemotherapy. The objective of this study was to evaluate febrile neutropenic episodes in children with malignancy. Material and Methods:Sixty-eight children who received chemotherapy for malignancy between 2010 and 2015 were retrospectively reviewed. The demographic characteristics, laboratory data, infection foci, and frequency of microorganisms grown in culture were examined. Also, the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
2
8
0
1
Order By: Relevance
“…The frequency of drug-related deaths identified in this study is 1.1%, which is consistent with that reported in the literature (0.1% to 13%) [32]; however, it is important to consider that there is wide variability in published values and that, as previously mentioned, ADR underreporting at HIMFG is 93.9% [38] and, thus, the problem might be underestimated. Antineoplastic and immunomodulating agents use and febrile neutropenia occurred more commonly in patients whose outcome was drug-related death, which has already been widely studied in patients on cancer treatment [49,50]. On the other hand, 0.7% of patients recovered with some sequel, which is consistent with previous reports in the literature [51].…”
Section: Plos Onesupporting
confidence: 89%
“…The frequency of drug-related deaths identified in this study is 1.1%, which is consistent with that reported in the literature (0.1% to 13%) [32]; however, it is important to consider that there is wide variability in published values and that, as previously mentioned, ADR underreporting at HIMFG is 93.9% [38] and, thus, the problem might be underestimated. Antineoplastic and immunomodulating agents use and febrile neutropenia occurred more commonly in patients whose outcome was drug-related death, which has already been widely studied in patients on cancer treatment [49,50]. On the other hand, 0.7% of patients recovered with some sequel, which is consistent with previous reports in the literature [51].…”
Section: Plos Onesupporting
confidence: 89%
“…Number of studies reporting the outcome(s) are indicated for each represented area. The total number of studies reporting the four assessed outcomes, respectively, were: test performance, N = 6 14,17,23,24,27,37 ; clinical course, N = 24 2,11,12,14–19,21,23,25,29,30,33,35–41,43 ; health outcomes, N = 21 2,11–13,15,18,19,22,26–29,31–33,35,36,39,41,43 ; and healthcare resource utilization (HCRU) and cost, N = 8 11,13,29,32,37,39,41,43 . *One study 37 that reported HCRU and cost, clinical course, and test performance is not shown on the Venn diagram.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review highlights distinct gaps in published data test performance, N = 6 14,17,23,24,27,37 ; clinical course, N = 24 2,11,12,[14][15][16][17][18][19]21,23,25,29,30,33,[35][36][37][38][39][40][41]43 ; health outcomes, N = 21 2,[11][12][13]15,18,19,22,[26][27][28][29][31][32][33]35,36,39,41,43 ; and healthcare resource utilization (HCRU) and cost, N = 8. 11,13,29,32,37,39,41,43 *One study 37 that reported HCRU and cost, clinical course, and test performance is not shown on t...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Период полувыведения СРБ составляет 19 ч и не меняется ни при каких условиях [26]. Считается, что уровень данного маркера прямо коррелирует со степенью тканевого повреждения [27].…”
Section: с-реактивный белокunclassified